Rational Design of a Composite Electrode to Realize a High‐Performance All‐Solid‐State Battery. Issue 12 (16th April 2019) - Kim, KyungSu; Park, Jesik; Jeong, Goojin; Yu, Ji‐Sang; Kim, Yong‐Chan; Park, Min‐Sik; Cho, Woosuk; Kanno, Ryoji
Abstract: A potential solid electrolyte for realizing all‐solid‐state battery (ASB) technology has been discovered in the form of Li10 GeP2 S12 (LGPS), a lithium superionic conductor with a high ionic conductivity (≈12 mS cm −1 ). Unfortunately, the achievable Li + conductivity of LGPS is limited in a sheet‐type composite electrode owing to the porosity of this electrode structure. For the practical implementation of LGPS, it is crucial to control the pore structures of the composite electrode, as well as the interfaces between the active materials and solid‐ electrolyte particles. Herein, the addition of an ionic liquid, N ‐methyl‐ N ‐butylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([Py14 ][TFSI]), is proposed as a pore filler for constructing a highly reliable electrode structure using LGPS. [Py14 ][TFSI] is coated onto the surface of LGPS powder through a wet process and a sheet‐type composite electrode is prepared using a conventional casting procedure. The [Py14 ][TFSI]‐embedded composite electrode exhibits significantly improved reversible capacity and power characteristics. It is suggested that pore‐filling with [Py14 ][TFSI] is effective for increasing contact areas and building robust interfaces between the active materials and solid‐electrolyte particles, leading to the generation of additional Li + pathways in the composite electrode of ASBs. Abstract : A solid performance : Ionic liquid is proposed as a pore filler in a composite electrode for constructing a high‐performance all‐solid‐state battery. The pore‐filling improves the contact area between the cathode materials and solid electrolyte particles and minimizes overpotential at the interfaces. In practice, the proposed all‐solid‐state battery exhibits comparable electrochemical performance to conventional lithium‐ion batteries at room temperature.